2018
DOI: 10.1123/jpah.2017-0035
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Participation in Sport/Exercise Among Adolescents and Young Adults With and Without Mild to Moderate Intellectual Disability

Abstract: The results support limited existing evidence regarding the low level of participation of children and young people with intellectual disability in sport/exercise compared with their peers. Future work on promoting sport/exercise and physical activity in children and young people with intellectual disability may play a role in helping to reduce the health inequalities experienced by people with intellectual disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
(36 reference statements)
0
22
0
Order By: Relevance
“…At the interpersonal level, sufficient parental support (e.g., parents’ company) [ 37 ] and positive parental beliefs of the benefits of PA for their child [ 41 ] were identified as family factors that influence PA frequency among children and adolescents with ID. In addition, positive social interactions with peers [ 11 , 52 ] and positive relationships with the coach [ 37 ] were identified as social network facilitators that influence PA frequency among children and adolescents with ID. At the environmental level, an exergaming context implemented at home or at school was identified as a facilitator that influenced MVPA among children and adolescents with ID [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the interpersonal level, sufficient parental support (e.g., parents’ company) [ 37 ] and positive parental beliefs of the benefits of PA for their child [ 41 ] were identified as family factors that influence PA frequency among children and adolescents with ID. In addition, positive social interactions with peers [ 11 , 52 ] and positive relationships with the coach [ 37 ] were identified as social network facilitators that influence PA frequency among children and adolescents with ID. At the environmental level, an exergaming context implemented at home or at school was identified as a facilitator that influenced MVPA among children and adolescents with ID [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the physiological and psychological health benefits associated with PA participation, previous studies reported that children with intellectual disabilities (ID) did not meet the PA guideline of at least 60 min of moderate-to-vigorous-intensity physical activity (MVPA) per day [ 7 , 8 , 9 ]. In addition, children and adolescents with ID are less active than their counterparts without disabilities [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concurrent with Scior and Werner (2015), we found that positive direct contact through leisure activities can help develop a stronger social presence in the community which challenge negative attitudes associated with learning disabilities. We consider this to be a positive and important step forward in reducing the disparity in physical activity uptake still evident between people who have a learning disability and their typically developing peers (Robertson et al, 2018). It is essential that we continue to foster positive relationships by integrating populations as the attitudes of others have been found to be a key facilitator in encouraging participation (Shields & Synnot, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that a limited access to equipment and facilities and the level of disability led to the fact that children performed PA less frequently [40]. The authors revealed that their worse image in the society, insufficient support of family and close friends, limited access to transport and the lack of knowledge about the possibilities to participate in sports have been playing a significant role and have constituted the reason for the lower participation in PA among children with disabilities [41][42][43][44][45]. On the other hand, it was observed that despite their disabilities that cause various complaints, children are aware of their functional capabilities and make use of available facilities to do sports or take up extra PA [46][47].…”
Section: Discussionmentioning
confidence: 99%